PREVENTIVE GERD WITH EDUCATION STRESS MANAGEMENT JELITA SMEs DURING THE COVID-19 PANDEMIC IN MANUKAN SURABAYA - Nur Jannah; Yurilla Endah Muliatie; Navik Kholili (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2021)
Gerd disease (Gastroesophageal Reflux Disease) is a chronic disease of the digestive system. This disease is closely related to lifestyle and easily recurs when the sufferer is under stress. Gerd occurs when stomach acid backs up into the esophagus or esophagus. As a result, the esophagus becomes irritated. Therefore, we collaborate with UKM Jelita intends to provide insight into preventing Gerd disease to UKM Jelita. UKM Jelita is an SME association run by the elderly who are approaching their fifties in the Manukan Rejo area of ​​Surabaya. As is known, during the Covid-19 pandemic, many businesses from UKM Jelita experienced a decline, although not drastically and resulted in gerd disease because they experienced stress. In addition to being stressed by the pandemic, they are also stressed by the decline in sales turnover. We as a service team intend to help prevent this gerd by educating about stress management. The method of implementation is by socializing Gerd's disease and how to overcome it. With this activity, it is hoped that Jelita SMEs can take preventive actions against Gerd disease.